Building assets, building credit creating wealth in low-income communities - Retsinas, Nicolas Paul, 1946-; Belsky, Eric S. (Brookings Institution Press, 2005)
"Examines the path from basic banking services to creditmaking decisions to mortgage lending that can give low-income individuals and communities the opportunity to build assets through credit, highlighting the need for transparency in the subprime market, buyer education, and borrower safeguards"--Provided by publisher.